Antibacterial, antioxidant and hypoglycaemic effects of Thymus capitatus (L.) Hoffmanns. et Link leaves' fractions. (June 2015) - Iauk, Liliana; Acquaviva, Rosaria; Mastrojeni, Silvana; Amodeo, Andrea; Pugliese, Michela; Ragusa, Monica; Loizzo, Monica R.; Menichini, Francesco; Tundis, Rosa
Abstract The aim of this study was to examine the bioactivity of the methanol fraction (MF) and n-hexane fraction (HF) of Thymus capitatus leaves in relation to their constituents analysed by gas chromatography and gas chromatography-mass spectrometry. The effects of T. capitatus on the growth of pathogenic bacteria associated with respiratory diseases (13 gram-positive and 4 gram-negative) were determined using a microdilution method. The MF was particularly effective on Streptococcus pneumoniae and Moraxella catarrhalis. The antioxidant activity was evaluated by 2, 2-diphenyl-1-picrylhydrazyl, 2, 2′-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid), ferric-reducing antioxidant power and β-carotene bleaching assays. A strong activity using β-carotene bleaching test was observed with the MF (IC50 of 0.7 μg/mL after 30 min of incubation). In the hypoglycaemic test, a selective α-amylase inhibitory activity was detected with the HF begging the most active (IC50 of 422.5 μg/mL). T. capitatus may represent a source of natural bioactive compounds.